Two way shape memory effect in acrylic (PMMA) - Teo, Chok Yong (Nanyang Technological University, 2023)
This research aimed to analyze the behavior of polymethyl methacrylate (PMMA) under controlled thermal cycling below its glass transition temperature (Tg). The study involved subjecting PMMA samples to thermal cycling using a Dynamic Mechanical Analyzer (DMA) Q800 while recording the resulting strain values. The analysis revealed interesting findings regarding the deformation characteristics of PMMA. Notably, the relationship between stress levels and strain values during cooling was observed, suggesting potential implications of stress on deformation. Moreover, the investigation indicated that variations in the young's modulus played a significant role in the observed behavior, potentially indicating the presence of a two-way shape memory effect (TSME). These findings highlight the importance of considering temperature, stress, and young's modulus in studying PMMA's deformation behavior. The research provides valuable insights into the thermomechanical coupling effect in PMMA.